2018
DOI: 10.15441/ceem.17.253
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of ascorbic acid on dapsone-induced methemoglobinemia in rats

Abstract: ObjectiveDapsone (diaminodiphenyl sulfone, DDS) is currently used to treat leprosy, malaria, dermatitis herpetiformis, and other diseases. It is also used to treat pneumocystis pneumonia and Toxoplasma gondii infection in HIV-positive patients. The most common adverse effect of DDS is methemoglobinemia from oxidative stress. Ascorbic acid is an antioxidant and reducing agent that scavenges the free radicals produced by oxidative stress. The present study aimed to investigate the effect of ascorbic acid in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 31 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…A prospective study conducted in rats compared single doses of ascorbic acid 15 mg/kg administered over 5 minutes, methylene blue 1 mg/kg, and placebo, and found a decrease in methemoglobin at 180 minutes in methylene blue (4.8%) and ascorbic acid (10%) compared with placebo (20.4%). 17 The authors concluded that while ascorbic acid was effective, it was not as effective as methylene blue and proposed that a higher dose might be required to achieve a similar decrease in methemoglobin levels. Our case report utilized a total dose of 8000 mg (116 mg/kg), which is significantly higher than the previously mentioned prospective study.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective study conducted in rats compared single doses of ascorbic acid 15 mg/kg administered over 5 minutes, methylene blue 1 mg/kg, and placebo, and found a decrease in methemoglobin at 180 minutes in methylene blue (4.8%) and ascorbic acid (10%) compared with placebo (20.4%). 17 The authors concluded that while ascorbic acid was effective, it was not as effective as methylene blue and proposed that a higher dose might be required to achieve a similar decrease in methemoglobin levels. Our case report utilized a total dose of 8000 mg (116 mg/kg), which is significantly higher than the previously mentioned prospective study.…”
Section: Discussionmentioning
confidence: 99%
“…For moderate-to-severe forms, ascorbic acid, which prevents haemoglobin conversion to methaemoglobin due to its antioxidant effects, as well as methylene blue are recommended, particularly in symptomatic cases with methaemoglobin levels above 20%. 3,6,7 In our series, methylene blue was administered in one pregnancy during emergency LSCS due to symptomatic presentation with methaemoglobin level above 40%. The teratogenic risk of methylene blue is negligible in this case as baby was delivered soon after its administration, consistent with a reported case.…”
Section: Discussionmentioning
confidence: 99%
“…Methylene blue is reduced to leukomethylene blue, which acts as an artificial electron donor to methemoglobin, thereby enhancing the ability of erythrocytes to reduce methemoglobin. Vitamin C has antioxidant effects on hemoglobin to prevent conversion to methemoglobin [ 2 , 3 ]. Our patient responded well to methylene blue and vitamin C, as evidenced by the increment in oxygen saturation as well as complete resolution of methemoglobinemia and hemolysis.…”
Section: Discussionmentioning
confidence: 99%